Microorganisms—An Effective Tool to Intensify the Utilization of Sulforaphane - Xiude Li; Yihan Wang; Guoping Zhao; Guangmin Liu; Pengjie Wang; Jinwang Li (Foods, 2022)
Sulforaphane (SFN) was generated by the hydrolysis of glucoraphanin under the action of myrosinase. However, due to the instability of SFN, the bioavailability of SFN was limited. Meanwhile, the gut flora obtained the ability to synthesize myrosinase and glucoraphanin, which could be converted into SFN in the intestine. However, the ability of microorganisms to synthesize myrosinase in the gut was limited. Therefore, microorganisms with myrosinase synthesis ability need to be supplemented. With the development of research, microorganisms with high levels of myrosinase synthesis could be obtained by artificial selection and gene modification. Researchers found the SFN production rate of the transformed microorganisms could be significantly improved. However, despite applying transformation technology and regulating nutrients to microorganisms, it still could not provide the best efficiency during generating SFN and could not accomplish colonization in the intestine. Due to the great effect of microencapsulation on improving the colonization ability of microorganisms, microencapsulation is currently an important way to deliver microorganisms into the gut. This article mainly analyzed the possibility of obtaining SFN-producing microorganisms through gene modification and delivering them to the gut via microencapsulation to improve the utilization rate of SFN. It could provide a theoretical basis for expanding the application scope of SFN.